Thermal and structural effects of amino acids on the interactions of thiamine hydrochloride with water - Khitismita Prusty; Prativa Kar; Braja B. Nanda; Binita Nanda (Chemical Thermodynamics and Thermal Analysis)
The viscosity, η, and density, ρ, of amino acids (AAs), l-Valine and Glycine dissolved in water with thiamine hydrochloride (vitamin B1) have been analysed at 5 unalike temperatures like “T= (298.15 to 313.15) K” and 0.1 MPa pressure. The “volumetric and viscometric properties” such as apparent molar volume, V2.ϕ, partial molar volume, Vϕ0, limiting molar expansivity, E2,ϕ0, relative viscosity, ηr, Jones-Dole constant, B, the Falkenhagen Coefficient, A, have been computed from the experimentally obtained viscosity and density values respectively. The main objective of the work to explore the presence the varieties of interactions present in the water, amino acids and vitamin B1 system by using the values of above parameters. The transfer volume, solvation number, nH of solutes have been computed. The effect of the zwitterionic group (NH3+, COO−)and CH2 chain length of amino acids on the values of B-coefficients, and V2ϕ0 have been obtained by their linear association as a function of the sum of “C “atoms in the alkyl groups of the considered solutes. In our research, the negative value of (∂E2,ϕ0/∂T)p and small positive values of viscosity B-coefficient represent the chaotropic nature of amino acids and they also undergo pair wise interactions with the vitamin B1. The nH values show that amino acids are hydrated in the present study. From the values of group contribution, we can predict that the Vϕ0, of l-valine > glycine in the said solutions.